2001
DOI: 10.1097/00124645-200109000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Service and Education Share Responsibility for Nursesʼ Value Development

Abstract: This article examines professional values of senior baccalaureate nursing students and practicing nurses. An important finding was that practicing nurses rated behaviors reflecting values in the American Nurses Association (ANA) Code for Nurses as more important than did senior students, thereby supporting the notion that practice contributes to value formation. The ongoing development and internalization of the nursing professions' values requires active involvement by staff development educators. The phenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 10 publications
3
55
1
2
Order By: Relevance
“…Overall, the literature suggests that the teaching of professional values to nurses theoretically starts in nursing schools but actually develops further over time with clinical practice. 20,21 Similarly, in some studies, although ethics education had a positive effect on professional values, it has been reported that students lack the basic knowledge regarding professional values and have different perspectives on the importance of professional values. 7,22 In this study, one of the reasons why young nurses with few working years received low scores may be related to not having sufficient experience.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, the literature suggests that the teaching of professional values to nurses theoretically starts in nursing schools but actually develops further over time with clinical practice. 20,21 Similarly, in some studies, although ethics education had a positive effect on professional values, it has been reported that students lack the basic knowledge regarding professional values and have different perspectives on the importance of professional values. 7,22 In this study, one of the reasons why young nurses with few working years received low scores may be related to not having sufficient experience.…”
Section: Discussionmentioning
confidence: 97%
“…[19][20][21][22] In Turkey, there are studies in the literature that focus on identifying students' professional values in general; however, due to the limited number of studies with nurses, conducting this study was deemed necessary. Its goals are to clarify two main sets of questions:…”
Section: Research Problem and Questionsmentioning
confidence: 99%
“…Nurses are expected to provide their patients with respectful, efficient and unbiased care 2 . Studies show that nurses and nursing students attach great importance to such concepts as respect, privacy, confidentiality, support and quality care, all of which are related to the dimension of caring 7,10 . In Taiwan, Lin et al studied the change in nursing students' perception of professional values between the times when they begin their studies and when they graduate with a bachelor's degree.…”
Section: Discussionmentioning
confidence: 99%
“…At the core of professional values is: honesty and integrity, humanity, respect, sense of responsibility, compassion and sympathy, altruism, self-confidence, and self-improvement Professional culture and education are among the factors that affect nursing values 4 . Attention to the global nursing culture is essential to the improvement of nurses' professional performance 9 .The impartment of professional nursing values is a gradual and longlasting process which begins with the professional education of nurses and extends throughout all the years of a nurse's practice 10 . Studies show that the majority of nurses find it challenging to act based on professional values and moral ideals in clinical environments 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation